2020
DOI: 10.1104/pp.19.01522
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Increases Zinc Bioavailability to Avoid Light-Mediated Reactive Oxygen Species Production under Zinc Deficiency

Abstract: Zinc (Zn) is an essential micronutrient for plant growth. Accordingly, Zn deficiency (2Zn) in agricultural fields is a serious problem, especially in developing regions. Autophagy, a major intracellular degradation system in eukaryotes, plays important roles in nutrient recycling under nitrogen and carbon starvation. However, the relationship between autophagy and deficiencies of other essential elements remains poorly understood, especially in plants. In this study, we focused on Zn due to the property that w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 44 publications
0
31
0
Order By: Relevance
“…Most ATGs were first identified and functionally characterized by mutagenesis studies in yeast [2]. More than 30 ATGs have now been identified in yeast, and 23, including ATG1-10, [12][13][14][16][17][18]20,27,29,31,TOR,VPS15,and VPS34, are considered to be the core ATGs participating in autophagy [3,4]. In Arabidopsis, around 40 homologues to these core ATGs have been identified, except for ATG14, 17,27,29, and 31 with no homologues [1,3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most ATGs were first identified and functionally characterized by mutagenesis studies in yeast [2]. More than 30 ATGs have now been identified in yeast, and 23, including ATG1-10, [12][13][14][16][17][18]20,27,29,31,TOR,VPS15,and VPS34, are considered to be the core ATGs participating in autophagy [3,4]. In Arabidopsis, around 40 homologues to these core ATGs have been identified, except for ATG14, 17,27,29, and 31 with no homologues [1,3].…”
Section: Discussionmentioning
confidence: 99%
“…Under heat stress, atg mutants of Arabidopsis displayed visibly impaired pollen development (including atg2-1, atg5-1, atg7-2, and atg10-1) [29] or enhanced growth inhibition (including atg2-1, atg5-1, atg12ab, and atg18a-2) [30]. Recently, Shinozaki et al proved that autophagy played important role in maintaining zinc bioavailability to avoid ROS accumulation under zinc deficiency in Arabidopsis [31]. Moreover, the potential roles of autophagy in waterlogging and excess aluminum and copper stresses were also reported [13,32,33].…”
Section: Introductionmentioning
confidence: 99%
“…During cell senescence, macromolecules tend to catabolize rather than synthesize, thus nutrient will be transferred to healthy cells (Avila-Ospina et al 2014;Qi et al 2020aQi et al ,2020bShinozaki et al 2020). For example, during bamboo shoot postharvest stage, pathways including autophagy, fatty acid degradation and amino acid metabolism upregulated, accompanied by organism senescence (Li et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Starvation is usually due to lack of certain nutrients, such as carbon/glucose or nitrogen, but Kawamata et al were the first to show that zinc deficiency can also be an autophagy trigger in yeast [68,69]. On the other hand, Shinozaki et al recently showed that autophagy maintained zinc pools increased zinc bioavailability and retained ROS homeostasis under zinc deficiency in plants [70]. These cases are not directly associated with the main subject of this review, but they show that autophagy, which is considered as an evolutionary conserved process, may be regulated by zinc and vice versa-zinc homeostasis can be regulated by autophagy.…”
Section: Zinc and Autophagymentioning
confidence: 99%